Association of Recreational Cannabis Legalization with Frequency of Using Cannabis for Sleep - Panchal, Zoë; Sakai, Joseph T.; Ellingson, Jarrod M.; Zellers, Stephanie; Wright, Kenneth P.; McGue, Matt K.; Vrieze, Scott; Hewitt, John K.; Corley, Robin P.; Iacono, William; Hopfer, Christian J.; Ross, J. Megan (Journal of psychoactive drugs, 2025)
We examined the association of recreational cannabis legalization (RCL) with frequency of using cannabis, alcohol, and sleep medication for sleep and with co-use of cannabis with other sleep aids. We used linear regression models to examine these associations in a population-based sample of adult twins ( = 3,141). Participants (M = 37 (SD = 5)) were primarily White (93%), with 5% Hispanic/Latinx, and female (61%). RCL was associated with using cannabis for sleep more frequently even after controlling for cohort, demographics, sleep quality, anxiety, depression, physical health, season, and pre-legalization cannabis use frequency (β = 0.123, = .001). RCL was not associated with frequency of using alcohol or sleep medication for sleep, or with co-use of cannabis and other sleep aids. More research is needed to determine whether RCL leads to more frequent use of cannabis for sleep.